Determination of ascorbic acid using multi-wall carbon nanotubes immobilized on carbon paste electrode - Vu, Dai Long; Sýs, Milan; Vytřas, Karel; Červenka, Libor (Univerzita Pardubice, 2012)
In this study, multi-wall carbon nanotubes (MWCNTs) immobilized on carbon paste electrode (CPE) was employed for the amperometric detection of ascorbic acid (AA). The influence of pH on the electrocatalytic effect of MWCNTs/CPE towards the oxidation of AA was studied; the effect of the potential applied and the stirring speed for amperometric detection of AA was investigated. The calibration curve was obtained for AA concentrations in a range of 1-100 μM. The detection limit for the method proposed was found to be 0.1 μM in the amperometric mode.
Keywords: carbon paste electrode; multi-wall carbon nanotubes; electrocatalytic oxidation; modified electrode; voltammetry; amperometry; determination; ascorbic acid